Evaluating the impact of adaptive signal control technology on driver stress and behavior using real-world experimental data. (October 2018) - Khattak, Zulqarnain H.; Fontaine, Michael D.; Boateng, Richard A.
Highlights: A real-world study was conducted to evaluate the impact of ASCT on driver stress and behavior. Participants traveled through two arterial corridors i.e. ASCT and non ASCT. Heart rate and driver behavior data was analyzed using ANOVA and Pearson correlation coefficient. ANOVA revealed statistically significant reduction in driver heart rate on ASCT corridor, translating to a reduced stress. Speeds were found to be negatively correlated with driver stress and it was concluded that ASCT creates positive improvements in driver stress and behavior. Abstract: While the operational and crash reduction benefits of adaptive signal control technology (ASCT) have long been investigated, the impact of this technology on driver behavior and stress is still uncertain. This study evaluated the impact of ASCT on driver behavior and stress in a real-world environment. Participants travelled through two arterial corridors, one equipped with ASCT and the other having traditional time-of-day coordinated signals. Driver stress was measured using a heart rate detector and a perceived stress scale while driver behavior was examined using vehicular trajectory data. Overall, driving behavior improved on the ASCT as compared to the non-ASCT corridor, as indicated by higher speeds and a fewer number of stops on the ASCT corridor relative to the non-ASCT corridor. Repeated measures ANOVA showed a statistically significant reduction in driver heart rate by −10 beats per minute over the ASCT corridor. A similar trend was observed for drivers' perceived stress, analyzed by Wilcoxon sign ranked test. Driving behavior also showed significant improvement with ASCT presence, and speed was found to be negatively correlated with stress. Furthermore, the participants' speed was controlled by the two systems i.e. ASCT and non-ASCT as expected. This study provides a significant proof of concept that ASCT can create positive improvements in driver stress and behavior that can be further investigated in the future.